Characteristics of the Euro, the Demand for Reserves, and Policy Coordination Under EMU - Masson, Paul.; Turtelboom, Bart. (Washington, D.C. : International Monetary Fund, 1997)
The success of European Economic and Monetary Union (EMU) will depend on the stability of the euro. The monetary policy framework is yet to be decided, but is likely to involve either money or inflation targeting. Stochastic simulations compare the outcomes for major macroeconomic and financial variables pre- and post-EMU under both policy rules, as well as under an inflation targeting rule that includes output. Implications for the euro as a reserve currency are examined in the light of the expected returns and covariances among reserve currencies. The role of the exchange rate as an indicator and incentives for policy coordination with other major countries are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet